Using a Systems Engineering Approach to Build a PCR Testing System at a Medical School During the COVID-19 Pandemic - Oba J; Toriya M; Uwamino Y; Matsuo K (Risk Management and Healthcare Policy, 2024)
Junna Oba,1 Masako Toriya,2 Yoshifumi Uwamino,3 Koichi Matsuo4 1Department of Extended Intelligence for Medicine, the Ishii-Ishibashi Laboratory, Keio University School of Medicine, Tokyo, Japan; 2Global Research Institute, Keio University, Tokyo, Japan; 3Department of Laboratory Medicine, Keio University School of Medicine, Tokyo, Japan; 4Collaborative Research Resources, Keio University School of Medicine, Tokyo, JapanCorrespondence: Masako Toriya, Global Research Institute, Keio University, 2-15-45 Mita, Minato-ku, Tokyo, 108-8345, Japan, Tel +81-3-5427-1379, Fax +81-3-5427-1703, Email masako.toriya@keio.jpBackground: During the COVID-19 pandemic, there was an increasing need to expand diagnostic testing in hospitals. At Keio University Hospital (KUH), clinical staff were concerned that the demand for PCR testing might exceed the capacity of the Clinical Laboratory. In response, basic researchers at Keio University School of Medicine (KUSM) set out to build a new, collaborative, PCR testing system. To be authorized to perform such diagnostic PCR testing, KUSM registered its core laboratory as an external clinical laboratory (ECL).Methods: In the pandemic, there was a pressure to build the PCR system quickly. Speed required discussions that developed a shared understanding of the unprecedented, new KUH/KUSM PCR system. To design, construct, and archive the new PCR testing system, we used a systems engineering (SE) approach. This included diagram visualization of functional flows and application of the Unified Architecture Framework (UAF), both of which are often used in system building. We considered daily demand for PCR testing at KUH and KUSM, and daily COVID-19 infections in Japan.Results: We operated the collaborative PCR testing system from August 2020 to June 2022. Given public health insurance reimbursement policies, KUH focused on individuals with suspicious symptoms, while the ECL at KUSM screened samples from asymptomatic individuals. KUSM performed about half as many tests as KUH. Interviewing KUH staff revealed that diagrams helped promote a better understanding of the KUH/KUSM PCR testing system.Conclusion: When designing temporary systems that may be repurposed in the future, we suggest using an SE approach with diagrams and UAF perspectives. This approach will enable stakeholders to understand what is being proposed to be built, and facilitate achieving an informed consensus on the proposed system. We suggest that SE approaches should be widely used in projects that involve building and operating complex, collaborative systems, and documenting the process. Keywords: COVID-19, PCR test, clinical laboratory, systems engineering, diagram, temporary system